Initiation of DNA replication in the dihydrofolate reductase locus is confined to the early S period in CHO cells synchronized with the plant amino acid mimosine. - Dijkwel, P A (1992)
In previous studies, we used two complementary two-dimensional gel electrophoretic methods to examine replication intermediates in the 240-kb amplified dihydrofolate reductase (DHFR) domain of methotrexate-resistant CHOC 400 cells (J. P. Vaughn, P. A. Dijkwel, and J. L. Hamlin, Cell 61:1075-1087, 1990). Surprisingly, in both asynchronous and early-S-phase cultures, initiation bubbles were detected in several contiguous fragments from a previously defined 28-kb initiation locus. However, because of the low levels of bubblelike structures observed on gels, it has been suggested that these structures might represent artifacts, possibly unrelated to replication per se. In this study, we have achieved much more synchronous entry into S phase by using a novel inhibitor and have isolated replication intermediates by a new procedure that largely eliminates branch migration and shear. Under these conditions, we find that (i) the relative number of bubblelike structures detected in fragments from the initiation locus is markedly increased, (ii) bubbles are detected at multiple sites scattered throughout the region lying between the DHFR and 2BE2121 genes, and (iii) bubbles appear and disappear in this region with the kinetics expected of an early-firing origin. These data strengthen the proposal that in vivo, initiation can occur at any of a large number of sites scattered throughout a broad zone in the DHFR domain.